Persepsi Mahasiswa Prodi PAI Angkatan 2022 terhadap Mata Kuliah Tashih Tilawah Al-Qur’an - Tri Afrida; Rahmi Wiza (ISLAMIKA, 2023)
The Quran is the most important source of Islamic law, Islamic education study program is one of the study programs that dominantly interacts with the Quran. but of course it becomes a problem if students of the Islamic education study program are unable to read the Quran, therefore a Tashhih Recitation of the Quran course is held to overcome this problem. However, Islamic education study program students have different responses and views on this subject. Therefore, this study aims to find out how the positive and negative perceptions of students towards the Tashhih Recitation of the Qur'an course. The method used is a qualitative research method, with data sources obtained through interviews with the heads of Islamic education study programs, supporting lecturers and students. To obtain the results of the interviews, use interview guidelines as a research instrument. In addition, data was also obtained through documentation. For data analysis techniques in the form of data reduction, data presentation and drawing conclusions. The findings in this study are; First, the positive perception of Islamic education study program students class of 2022 regarding the Tashhih Recitation of the Quran course includes: a) the Tashhih Recitation of the Quran course as a place for learning the Quran. b) learning Tashhih Recitations of the Quran means fulfilling obligations towards the Koran. c) learning Tashhih Recitations of the Quran improves the quality of reading the Quran. d) learning Tashhih Recitations of the Quran to avoid changes in meaning and meaning when reading the Quran. The two positive perceptions of Islamic Religion Study Program students class of 2022 regarding the Tashhih Recitation of the Quran include: a) the learning methods used do not vary. b) study schedule is not fixed. c) short study time. d) the capacity of students is too much.